2021
DOI: 10.15446/dyna.v88n218.91077
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of alluvial soil hydrodynamics in the upper Ipanema river basin using the Beerkan method

Abstract: The objective was to model the spatial distribution of the physical properties of the soil through geostatistics in the Brazilian semi-arid region. The study was carried out in the Experimental Basin of Ipanema River, Pernambuco, in an alluvial area with regular grid and samples of 40 points. Infiltration tests were carried out to assess hydraulic conductivity and sampling was performed to determine soil texture and soil organic carbon (SOC). The variables were subjected to descriptive and correlation statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Similar results were obtained by [40], who analyzed the effect of rice straw mulch on soil temperature in irrigated vine cultivation in the Loess plateau, China, and found that the mulch reduced soil temperature during warmer periods and kept it higher in colder periods when compared to bare soil. [28] studied 4 different mulch types (wood dust, wood chips, dry grass (Cynodon spp.) and rice straw) in carrot cultivation and observed statistically significant differences.…”
Section: Temperature At the Soil Surfacementioning
confidence: 99%
“…Similar results were obtained by [40], who analyzed the effect of rice straw mulch on soil temperature in irrigated vine cultivation in the Loess plateau, China, and found that the mulch reduced soil temperature during warmer periods and kept it higher in colder periods when compared to bare soil. [28] studied 4 different mulch types (wood dust, wood chips, dry grass (Cynodon spp.) and rice straw) in carrot cultivation and observed statistically significant differences.…”
Section: Temperature At the Soil Surfacementioning
confidence: 99%